2018
DOI: 10.1186/s12934-018-1018-4
|View full text |Cite
|
Sign up to set email alerts
|

The pleiotropic effects of the glutamate dehydrogenase (GDH) pathway in Saccharomyces cerevisiae

Abstract: Ammonium assimilation is linked to fundamental cellular processes that include the synthesis of non-essential amino acids like glutamate and glutamine. In Saccharomyces cerevisiae glutamate can be synthesized from α-ketoglutarate and ammonium through the action of NADP-dependent glutamate dehydrogenases Gdh1 and Gdh3. Gdh1 and Gdh3 are evolutionarily adapted isoforms and cover the anabolic role of the GDH-pathway. Here, we review the role and function of the GDH pathway in glutamate metabolism and we discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 118 publications
(213 reference statements)
0
34
0
Order By: Relevance
“…Low temperature diminished the concentrations in the wine strain but increased it in the laboratory strain. As mentioned earlier, overexpression of this protein may be detrimental at low temperatures due to a NADH-NAD imbalance 33 . However, a downward shift in the growth temperature also induced an oxidative stress response.…”
Section: Response Of Cenpk Strain Versus Ady5 Strainmentioning
confidence: 82%
See 2 more Smart Citations
“…Low temperature diminished the concentrations in the wine strain but increased it in the laboratory strain. As mentioned earlier, overexpression of this protein may be detrimental at low temperatures due to a NADH-NAD imbalance 33 . However, a downward shift in the growth temperature also induced an oxidative stress response.…”
Section: Response Of Cenpk Strain Versus Ady5 Strainmentioning
confidence: 82%
“…In addition, isoleucine has been described as part of a set of amino acids typically abundant in thermophilic organisms, contributing to a high thermal stability of proteins 30 . Likewise, Mara and co-authors observed that overexpression of Gdh1 had detrimental effects on yeast growth at 15 ºC 31 . The GDH pathway is involved in the recycling of NADH-NAD by controlling the levels of α -ketoglutarate.…”
Section: Strain-specific Responses To Sub-and Supra-optimal Temperaturementioning
confidence: 89%
See 1 more Smart Citation
“…Several reviews exist that focus on yeast nitrogen sensing, signalling, transport, assimilation and metabolism [27][28][29][30][31][32][33][34][35]. A general conclusion is that yeast growth rate is not only associated with the amount of available nitrogen, but also with the quality of the nitrogen source [18,27].…”
Section: Yeast Nitrogen Utilization Under Wine Fermentative Conditionsmentioning
confidence: 99%
“…We also observed an activation of the glutamate dehydrogenase (GDH) pathway, indicated by the upregulation of the ammonia permease coding gene YGR121C (MEP1), YOR375C (GDH1) and YOR375C (GDH3), coding for two NADP-dependent GDH isoforms for glutamate synthesis, and the glutamine synthase (GS) gene YPR035W (GLN1), and for the reduced expression of YDL215C (GDH2), another NADP-dependent GDH responsible for glutamate degradation. The GDH pathway is known to be regulated by the quality and availability of nitrogen and carbon sources 77 . Upon exposure to 800 mg L −1 of GN, two of the main regulators of the nitrogen catabolite repression (NCR) pathway, YFL021W (GAT1) and YER040W (GLN3) appear overexpressed as well as two of the main regulators associated to sugar catabolite repression (YGL035C) MIG1 and (YGL035C) GAL80.…”
Section: Scientific Reports |mentioning
confidence: 99%